2013
DOI: 10.1039/c3ce40749g
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration mechanism of a small molecular solid: 5-nitrouracil hydrate

Abstract: Previous studies of the dehydration of 5-nitrouracil (5NU) have resulted in it being classified as a ‘‘channel\ud hydrate’’ in which dehydration proceeds principally by the exit of the water molecules along channels in\ud the structure. We have re-examined this proposal and found that in fact there are no continuous channels\ud in the 5NU structure that would contribute to such a mechanism. Product water molecules would be\ud immediately trapped in unlinked voids in the crystal structure and would require some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…As already mentioned, it has been observed that the dehydration kinetic parameters can be strongly affected by various sample and experimental factors . Differences of the sample particle size, crystal habit, sample history, and crystal defect distribution can result in different dehydration rates, E a variation, and even change the kinetic model. Besides these factors, all the mentioned kinetic parameters can be affected by the relative humidity, inert gas flow rate, and sample weight .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, it has been observed that the dehydration kinetic parameters can be strongly affected by various sample and experimental factors . Differences of the sample particle size, crystal habit, sample history, and crystal defect distribution can result in different dehydration rates, E a variation, and even change the kinetic model. Besides these factors, all the mentioned kinetic parameters can be affected by the relative humidity, inert gas flow rate, and sample weight .…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Differences of the sample particle size, [28][29][30][31][32] crystal habit, 33 sample history, 25 and crystal defect distribution 24 can result in different dehydration rates, E a variation, and even change the kinetic model. Besides these factors, all the mentioned kinetic parameters can be affected by the relative humidity, 31,32,[34][35][36] inert gas flow rate, 31,34 and sample weight. 28,37 Thus, for the better understanding of the dehydration process and calculated kinetic parameters, the effects of sample and experimental factors should be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphism occurs commonly among drugs and different polymorphs always present distinct physical and chemical attributes, such as compressibility, melting point, crystal habit, color, density, dissolution rate, and solubility. Accordingly, in order to explore the polymorphism landscape and to optimize the solid-state properties, thorough polymorph screening and solid-state characterization of drug candidates are routinely conducted throughout the drug development process. The most common polymorph screening methods are crystallization from melt, vapor and cooling, evaporating, antisolvent, and slurrying with different solvents and at different temperatures. In addition, dehydration is an effective method for polymorph screening and some polymorphs can be prepared only by this conversion …”
Section: Introductionmentioning
confidence: 99%
“…Different mechanistic descriptions of dehydration such as nucleation and growth and 1D/2D/3D diffusion have led to the development of kinetic models, which are usually empirically fitted to experimental data such as thermal gravimetric analysis (TGA) data. Again, the results are often not suitable to discriminate between different dehydration models since many of them fit the data equally well. , …”
mentioning
confidence: 99%
“…Again, the results are often not suitable to discriminate between different dehydration models since many of them fit the data equally well. 5,6 Theoretical techniques can be used to obtain a great deal of insight into the energetics and related properties of crystalline materials. 7−10 Common density functional theory (DFT) simulations are not the most suitable computational approach to effectively probe the mechanistic aspect of hydration, as they typically can only be used to determine the energies of the lowest energy structures.…”
mentioning
confidence: 99%